Inflammasome genetic variants are associated with tuberculosis, HIV-1 infection, and TB/HIV-immune reconstitution inflammatory syndrome outcomes - de Sá, Nathalia Beatriz Ramos; de Souza, Nara Cristina Silva; Neira-Goulart, Milena; Ribeiro-Alves, Marcelo; Da Silva, Tatiana Pereira; Pilotto, Jose Henrique; Rolla, Valeria Cavalcanti; Giacoia-Gripp, Carmem B. W.; de Oliveira Pinto, Luzia Maria; Scott-Algara, Daniel; Morgado, Mariza Gonçalves; Teixeira, Sylvia Lopes Maia (Frontiers in Cellular and Infection Microbiology, 2022)
Background Tuberculosis (TB) and AIDS are the leading causes of infectious diseases death worldwide. Here, we investigated the relationship between from single nucleotide polymorphisms (SNPs) of the NLRP3, CARD8, AIM2, CASP-1, IFI16, and IL-1β inflammasome genes, as well as the profiles of secreted proinflammatory cytokines (e.g., IL-1β, IL-18, IL-33, and IL-6) with the TB clinical profiles, TB-HIV coinfection, and IRIS onset. Methods The individuals were divided into four groups: TB-HIV group (n=88; 11 of them with IRIS), HIV-1 group (n=20), TB group (n=24) and healthy volunteers (HC) group (n=10), and were followed up at INI/FIOCRUZ and HGNI (Rio de Janeiro/Brazil) from 2006 to 2016. Real-time PCR was used to determine the genotypes of the Single Nucleotide Polymorphism (SNPs), and ELISA was used to measure the plasma cytokine levels. Unconditional logistic regression models were used to perform risk estimations. Results A higher risk for extrapulmonary TB was associated with the TT genotype (aOR=6.76; P=0.026) in the NLRP3 rs4612666 Single Nucleotide Polymorphism (SNP) and the C-C-T-G-C haplotype (aOR=4.99; P= 0.017) in the NLRP3 variants. This same Single Nucleotide Polymorphism (SNP) was associated with lower risk against extrapulmonary TB when the carrier allele C (aOR=0.15; P=0.021) was present. Among those with HIV-1 infections, a higher risk for TB onset was associated with the GA genotype (aOR=5.5; P=0.044) in the IL1-β rs1143634 Single Nucleotide Polymorphism (SNP). In contrast, lower risk against TB onset was associated with the A-G haplotype (aOR=0.17; P= 0.026) in the CARD8 variants. Higher IL-6 and IL-33 levels were observed in individuals with TB. A higher risk for IRIS onset was associated with CD8 counts ≤ 500 cells/mm3 (aOR=12.32; P=0.010), the presence of extrapulmonary TB (aOR=6.6; P=0.038), and the CT genotype (aOR=61.06; P=0.026) or carrier allele T (aOR=61.06; P=0.026) in the AIM2 rs2276405 Single Nucleotide Polymorphism (SNP), whereas lower risk against IRIS onset was associated with the AT genotype (aOR=0.02; P=0.033) or carrier allele T (aOR=0.02; P=0.029) in the CARD8 rs2043211 Single Nucleotide Polymorphism (SNP) and the T-G haplotype (aOR=0.07; P= 0.033) in the CARD8 variants. No other significant associations were observed. Conclusions Our results depict the involvement of genetic polymorphisms of crucial innate immunity genes and proinflammatory cytokines in the clinical outcomes related to TB-HIV coinfection.